2015
DOI: 10.1093/jpepsy/jsv104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Drowning Prevention Program Based on Testimonial Videos: A Randomized Controlled Trial

Abstract: The testimonial-based intervention's efficacy appears promising, as it improved safety knowledge and simulated risk behaviors with water among rural Chinese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The Activity Room extends existing measures in a few ways. Existing vignette or dollhouse simulations are valuable to assess risk-taking (e.g., Morrongiello & Rennie, 1998; Schwebel et al, 2011; Shen et al, 2016), but are designed to measure intent to risk-take rather than actual risk-taking. The balance beam task developed by Morrongiello and Matheis (2007) successfully measured children’s physical risk-taking but was limited to a single task and targeted toward an older age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Activity Room extends existing measures in a few ways. Existing vignette or dollhouse simulations are valuable to assess risk-taking (e.g., Morrongiello & Rennie, 1998; Schwebel et al, 2011; Shen et al, 2016), but are designed to measure intent to risk-take rather than actual risk-taking. The balance beam task developed by Morrongiello and Matheis (2007) successfully measured children’s physical risk-taking but was limited to a single task and targeted toward an older age group.…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies to assess children's risk-taking use simulation. Several laboratories have simulated risk situations with virtual reality (e.g., pedestrian street-crossing among children aged 7 to 9; Dixon et al, 2020;Morrongiello et al, 2015;Schwebel et al, 2008Schwebel et al, , 2014Schwebel et al, , 2016 or with short vignettes, stories, or dollhouse simulations, usually among children ranging from 3 to 10 years old, that assess intended rather than actual risk-taking (e.g., Morrongiello & Rennie, 1998;Schwebel et al, 2011;Shen et al, 2016). Both virtual reality (Schwebel et al, 2008) and laboratory replications with stories or dollhouse scenarios (Morrongiello, Schwebel, et al, 2013) have demonstrated convergence with real-world behaviors.…”
mentioning
confidence: 99%
“…Children engaged in a structured task using dolls and toy vehicles on a small floor-based model village. Modeled after previous work [ 14 , 15 ], the task was designed to simulate and therefore assess children’s behavioral intentions in a variety of situations that replicate the lessons they might have learned on the Otto the Auto website. Specifically, children engaged in an interactive “story” guided by researchers.…”
Section: Methodsmentioning
confidence: 99%
“…Decrease in risk of drowning [58] Education materials No change in non-fatal drowning incidence [59] Increase in knowledge; [59] increase in knowledge; [60] increase in perception of drowning risk [66] Workshops Increase in water safety knowledge; [63] increase in water safety knowledge [64] Video testimonials Improved knowledge and simulated water behaviors [62] Lectures Reduction in mortality rates; [65] decrease in incidence of non-fatal drowning [67] Change in parental knowledge [65] The outcomes reported may be a summary of more than one intervention type.…”
Section: Education (Education) Training Of Community Health Workersmentioning
confidence: 99%